Chiral phosphoric acid-catalyzed enantioselective aza-Friedel-Crafts alkylation of indoles with γ-hydroxy-γ-lactams - Thibaut Courant (2018)
An enantioselective aza-Friedel-Crafts reaction of indoles with γ-hydroxy-γ-lactams using a chiral phosphoric acid catalyst is reported. The approach described herein provides an efficient access to 5-indolylpyrrolidinones in good to quantitative yields and excellent enantioselectivities (up to >99% ee). The results suggest that the reaction may proceed via N-acyliminium intermediates associated with the chiral phosphoric acid anion. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.